Outcomes of tunneled internal jugular venous catheters for chronic haemodialysis at the University College Hospital, Ibadan, Nigeria. (2018)
Introduction: vascular access is an important aspect of haemodialysis treatments and determinant of patient outcomes. Arteriovenous (AV) fistula has been described as the preferred haemodialysis vascular access for patients on chronic dialysis. There continues to be a challenge with the creation of AV fistula, due to shortage of vascular surgeons skilled in the AV fistula creation particularly in source limited setting. We described the outcomes of the tunneled internal jugular venous catheters amongst our patients at the University College Hospital (UCH) Ibadan. Methods: a retrospective study of patients on maintenance haemodialysis at the UCH, Ibadan, we reviewed the records of all patients on chronic dialysis over a period of 5 years. Information obtained include demographics, types and aetiology of renal failure, types of vascular access, observed complications and outcomes. Results: a total number of 147 catheters were inserted during the period under review, 94 were males while 53 were females. The age range was 18-85 years while the mean age was 46.3 ± 17.2 years. The range and mean duration for Tunneled Dialysis Catheter (TDC) carriage were (30 - 1,440) and 220±185 days respectively. The observed immediate complications of TDCs were failed first attempt 7(4.7%), reactionary haemorrhage 5(3.4%), arrhythmia 3(2.0%), haemothorax 2(1.4%) while death during catheter placement was recorded in 2(1.4%) cases. Catheter related infection was the commonest long-term complications and occurred in 15 cases (10.1%), while being diabetic increased the risk of developing catheter related complications. One tenth of our patients with End Stage Renal Disease on TDC had kidney transplantation while catheter related mortality was 16.3%. Conclusion: internal jugular tunneled dialysis catheters despite its shortcomings, has been a safe procedure with good outcomes among our patients on maintenance haemodialysis.